Portrayal of Quarter Life Crisis through The Use of Satire in The Song Lyrics “24” by Sundial - Kartika, Dilah Ratna (Edulitics (Education, Literature, and Linguistics) Journal, 2022)
This study analyzed how a quarter-life crisis is portrayed through the use of satire in the song lyrics "24" by Sundial. This study aimed to identify signs of a quarter-life crisis by describing the satire used in the song lyrics. Researchers used the content analysis method presented in TEEL paragraphs to portray the quarter-life crisis signs depicted in the satire song lyrics. The data were taken from the song lyrics "24" by Sundial, which was released in 2021. The result showed that there are six unrepeated stanzas of satire containing the portrayal of quarter-life crisis signs, dominated by the sign of feeling unhappy with the current life situation. The type of satire in this song is Menippean satire referring to a single object who is 24 years old. Other literary techniques are used to support the satire in this song, which is dominated by irony. This study emphasized how satire can portray inexpressible life problems like quarter-life crises through humor.